Effect of Different Mulching Materials on Leaf Spot Disease of Groundnut - Wagle, Pramod; Yadav, Bisheshwar Prasad; Rasaily, Santosh; Bhattarai, Sovika; Dahal, Biplav (International Journal of Applied Sciences and Biotechnology, 2023)
A study was conducted in summer season of 2020 and 2021 to evaluate the effect of different mulching materials on late leaf spot disease of groundnut caused by Phaeoisariopsis personata (Berk. & Curt.) v. Arx at Oilseed Research Program, Sarlahi, Nepal. The experiment was laid out in randomized complete block design (RCBD) with 7 treatments viz. rice husk, rice straw, black polythene sheet, Lantana camara, living mulch, sawdust and control in three replications with fertilizer dose 20:40:20 NPK kg per hectare. The disease was scored in 1-9 scale and severity and AUDPC was calculated. In 2020, Lantana camara mulched plot showed significantly the lowest disease severity and the lowest AUDPC value (66.67% and 1556) followed by rice husk (70.37% and 1556) and black plastic (70.37% and 1611) mulched plot. Similarly in 2021, Lantana camara mulched plot showed significantly lowest disease severity and the lowest AUDPC value (62.96% and 1500) followed by rice husk (66.67% and 1574) and black plastic (66.67% and 1574) mulched plot. Significantly the highest pod yield was obtained in rice husk mulched plot (2.35 t/ha in 2020 and 2.07 t/ha in 2021) followed by living mulch treated plot (2.13 t/ha in 2020 and 1.84 t/ha in 2021). The highest disease severity (81.4% same as rice straw and saw dust mulched plot) with highest AUDPC value (1981) was observed in plot with no mulch during 2020 where as in 2021, the highest disease severity (77.78 same as plot with no mulch) with highest AUDPC value (1889) was observed in rice straw mulched plot. This study shows that organic mulches like rice husk could be better option for reducing disease severity with better yield in groundnut. Int. J. Appl. Sci. Biotechnol. Vol 11(1): 37-41.